2018
DOI: 10.1002/ijgo.12494
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictive factors of early postpartum diabetes among women with gestational diabetes in a single‐center cohort

Abstract: The high prevalence of diabetes supports early postpartum oral glucose tolerance testing. Several women had undiagnosed diabetes. The risk factors identified could be useful for prenatal risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…In previous South African studies, a FPG has been shown very effective in detecting GDM; and identifying Type 2 diabetes early post-partum [11,28]. Good clinical accuracy was documented for POCT in the fasting state in the index study and fasting measurements were also close to the rigorous laboratory requirements for analytical accuracy.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…In previous South African studies, a FPG has been shown very effective in detecting GDM; and identifying Type 2 diabetes early post-partum [11,28]. Good clinical accuracy was documented for POCT in the fasting state in the index study and fasting measurements were also close to the rigorous laboratory requirements for analytical accuracy.…”
Section: Discussionmentioning
confidence: 63%
“…Physiological adaptations, implicated in the biochemical inaccuracy during gestation, are expected to revert soon after delivery [30]. Additionally, the postpartum population in this study has a high prevalence of Type 2 diabetes [11]. It is known that POCT devices do not perform consistently across glucose ranges [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations